Problem-Based Online Learning Assissted by Whatsapp to Facilitate The Scientific Learning of 2013 Curriculum - Pri Ariadi Cahya Dinata; Suparwoto Suparwoto; Desy Kumala Sari (Universitas Lambung Mangkurat, 2020)
Scientific learning is difficult to be applied in an ideal way because of the lack of learning time. One of the solutions to overcome it is by using blended learning that integrated into problem-based learning. This study aims to comprehend the effectivity of problem-based online learning (PBOL) to improve learning outcomes, and it’s efficiency to reduce the time of face to face learning. The used media was WhatsApp because of its simplicity, and the students have been familiar with it. The seventy students of the 10th grade of SMAN 1 Kelua were being sampled in this study based on a saturation sampling technique and divided into three classes. This was a quasi-experimental study with single factor multiple-treatment design. The premier data of this study were learning outcomes and the total time of learning in the class. The data of learning outcomes were obtained by test and be analyzed by one-way ANOVA to detect the effect of PBOL on the learning outcomes. The data of learning time were gained by observation and documentation and be analyzed in a descriptive way to know the efficiency of PBOL. The analyzed result showed sig. value is 0.04, that is means PBOL, and PBL produces learning outcomes which have significantly different from conventional learning. On the other side, even the learning outcomes of PBOL is equal as learning outcomes of PBL, and it’s learning time is fewer than the PBL’s. From both of the facts, we can conclude that the PBOL assisted by WhatsApp is effective in enhancing learning outcomes and more efficient to be used.